1993
DOI: 10.1159/000211133
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Pharmacokinetics and Metabolism of Prednicarbate after Cutaneous and Oral Administration

Abstract: Prednicarbate (PC) is a nonhalogenated derivative of prednisolone which is used for the local treatment of corticoid-sensitive skin diseases. In this study, the pharmacokinetics and the metabolism of PC in humans are investigated after cutaneous ointment application (75 mg PC) and after systemic oral administration (40 mg PC) in 8 healthy volunteers. In addition, the possible suppression of endogenous cortisol secretion by both application forms was monitored. After oral administration no intact PC, but signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Prednicarbate is rapidly hydrolyzed at position C 21 . The resulting intermediary product, prednisolone-17-ethylcarbonate, metabolizes slowly into prednisolone (47).…”
Section: Cross-reactivity Patternsmentioning
confidence: 99%
“…Prednicarbate is rapidly hydrolyzed at position C 21 . The resulting intermediary product, prednisolone-17-ethylcarbonate, metabolizes slowly into prednisolone (47).…”
Section: Cross-reactivity Patternsmentioning
confidence: 99%
“…Pharmacokinetic studies, including experiments concerning biotransformation in animals [32] and humans, [33] have revealed that prednicarbate is metabolised to prednisolone 17 -ethylcarbonate and then to prednisolone in the skin as well as in the liver, [34]lungsI35] and synovial tissue. [36,37] The former step is considerably faster than the latter one.…”
Section: Prednicarbatementioning
confidence: 99%
“…Prednicarbate is a non-halogenated derivative of prednisolone (prednisolone-17-ethyl carbonate-21-propionate), which is used for the local treatment of skin diseases responsive to topical glucocorticoids. It has good local efficacy and low systemic side effects (23).…”
Section: Methodsmentioning
confidence: 99%